Hygienic assessment of the potential risk for public health caused by groundwater and surface water pollution by pesticides of various chemical classes - Korshun, M.M.; Martіianova , Y.V. (Medicni Perspektivi, 2022)
The aim of the study was to compare the potential danger for human health caused by pollution in both underground and surface water sources with the fungicide pydiflumetofen and herbicides amicarbazone and bicyclopyrone in a wide range of soil-climatic conditions. Three methods were used: determination of the integral hazard vector (R); predicting the negative impact of pesticides on the health of the population by integral groundwater contamination hazard index (IGCHI), and a comprehensive risk assessment of the negative effects of pesticides on human body, when they are washed out into water (Р). It was found that the highest level of danger for public health due to possible pollution of water sources, is inherent in bicyclopyrone regardless of the soil-climatic conditions and the used assessment method (R=144.6-173.2 – very high potential hazard; IGCHI=12 points – extremely dangerous for humans, 1А class). Pydiflumetofen has a high potential integral vector hazard (R=115.8-137.5) and simultaneously by the value of the IGCHI (7-9 points) can be assessed from dangerous (2 class) to highly dangerous (1B class) for humans, depending on soil-climatic conditions. Amicarbazone by IGCHI (11 points) is extremely dangerous for humans (1A class), and at the same time by the integral vector (R=76.8-122.5) its potential danger varies from medium to high, depending on the soil-climatic conditions. Assessing the risk of the investigated pesticides, based on the comparison between potential exposure and the permissible daily intake it was concluded that the potential risk of adverse effects on public health (P) of all investigated substances is acceptable.